2021
DOI: 10.3389/fmicb.2021.647921
|View full text |Cite|
|
Sign up to set email alerts
|

Higher Abundance of Sediment Methanogens and Methanotrophs Do Not Predict the Atmospheric Methane and Carbon Dioxide Flows in Eutrophic Tropical Freshwater Reservoirs

Abstract: Freshwater reservoirs emit greenhouse gases (GHGs) such as methane (CH4) and carbon dioxide (CO2), contributing to global warming, mainly when impacted by untreated sewage and other anthropogenic sources. These gases can be produced by microbial organic carbon decomposition, but little is known about the microbiota and its participation in GHG production and consumption in these environments. In this paper we analyzed the sediment microbiota of three eutrophic tropical urban freshwater reservoirs, in different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 108 publications
(141 reference statements)
1
6
0
Order By: Relevance
“…The community composition of MOB in lake sediments has so far mainly been studied by microbial enrichment and isolation methods (e.g., Auman et al, 2000;He et al, 2012;Danilova et al, 2016), and by cultivation-independent methods involving fluorescence-in-situ-hybridization (FISH; Rahalkar et al, 2009), sequencing of 16S rRNA genes (Fiskal et al, 2021;Pierangeli et al, 2021), and sequencing of catabolic functional genes (for reviews see (McDonald et al, 2008;Knief, 2015). Hereby pmoA, a functional gene that encodes the catalytic subunit of particulate methane monooxygenase (pMMO), an enzyme which performs the initial conversion of methane to methanol, has been widely targeted.…”
Section: Introductionmentioning
confidence: 99%
“…The community composition of MOB in lake sediments has so far mainly been studied by microbial enrichment and isolation methods (e.g., Auman et al, 2000;He et al, 2012;Danilova et al, 2016), and by cultivation-independent methods involving fluorescence-in-situ-hybridization (FISH; Rahalkar et al, 2009), sequencing of 16S rRNA genes (Fiskal et al, 2021;Pierangeli et al, 2021), and sequencing of catabolic functional genes (for reviews see (McDonald et al, 2008;Knief, 2015). Hereby pmoA, a functional gene that encodes the catalytic subunit of particulate methane monooxygenase (pMMO), an enzyme which performs the initial conversion of methane to methanol, has been widely targeted.…”
Section: Introductionmentioning
confidence: 99%
“…When assessing the methane cycle microbial actors, recent studies observed the absence of relationships between the abundances of methanogens and/or methanotrophs and the recorded activity rates of fluxes (Emerson et al., 2021; Pierangeli et al., 2021), making these descriptors weak predictors of the methane cycle activity rates. Opposite, bacterial community composition was shown to significantly influence methanogenic community activity, particularly through the strong relationships occurring between fermentative bacteria and methanogenic archaea (Bertolet et al., 2019; Emerson et al., 2021; Lavergne et al., 2021; Pierangeli et al., 2021), with fermentative bacteria supplying substrates to methanogenic archaea, thus supporting trophic cooperation. At horizontal scales, methanogenic communities are generally different between low and high water depth areas, with site‐related changes in the relative abundances of the major genera (Berberich et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Some recent studies have highlighted similar methanogenesis pathways of Bathyarchaeota species to those of some methanogens (e.g., Methanomassiliicoccales ) [ 33 , 86 , 96 ]. In addition, these species are capable of performing anaerobic mineralization of proteins and anaerobic CH 4 oxidation [ 97 , 98 ]. The RDA and correlation analysis revealed negative relationships between pH and MBG–D/DHVEG–1 and positive relationships between DOC and MBG–D/DHVEG–1 (Fig.…”
Section: Discussionmentioning
confidence: 99%